Exploiting TRIZ Tools for enhancing systematic conceptual design activities. (3rd June 2018) - Fiorineschi, Lorenzo; Frillici, Francesco Saverio; Rotini, Federico; Tomassini, Marco
Abstract: Systematic design methods are widely diffused in academia, representing a standard in many engineering courses. Nevertheless, some flaws related to the conceptual design phase have been ascribed to these methods, especially concerning a non-comprehensive support to innovation. However, literature acknowledges several creativity-enhancing tools that can be conveniently combined with systematic design methods. In particular, many scholars refer to TRIZ, i.e. the well-known Russian problem-solving theory. Moreover, recent literature contributions propose some alternatives to the classical Functional Decomposition and Morphology (FDM), claiming to overcome some of the related flaws. One of them is the Problem Solution Network (PSN) approach, i.e. a systematic conceptual design method strongly based on a problem-solution co-evolutionary logic. In this context, our work aims at combining the potentialities of TRIZ with the benefits claimed for the PSN, by proposing a comprehensive integration procedure. Accordingly, this paper reports a detailed description of the proposal, where TRIZ tools are exploited to support problem solving within the PSN approach. Furthermore, an application is also reported where an industrial case study is presented to argue about possible potentialities and lacks of the proposed approach.